2005
DOI: 10.1002/mus.20361
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of paraneoplastic neuropathy with anti‐disialosyl antibody

Abstract: We report a paraneoplastic neuropathy with severe motor involvement following sensory-ataxic disturbance. Anti-disialosyl immunoglobulin M (IgM) antibody was detected in the course of malignant lymphoma of diffuse large B-cell type, which usually spares the motor system. Onset was subacute, with relapsing and remitting sensory ataxia, muscle weakness, bulbar palsy, respiratory paralysis, and ophthalmoplegia; only neck rotation was retained in the terminal stage. Autopsy showed no lymphoma cells infiltrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…undetected lymphoma) developed fatal EBV+ intracerebral lymphoma after treatment with various courses of immunotherapy [46]; analyses of intrathecal and peripheral M-protein as well as brain immunocytochemical studies suggested a common clonal origin of both immunoblastic cerebral proliferation and the serum paraprotein-secreting cells. Presumably, immune deficiency due to monoclonal B-cell proliferation and/or immunosuppressive therapy resulted in EBV-reactivation and dysregulation of CNS-restricted T-cell control of B-cell proliferation; autopsy did not include search for systemic lymphoma; (c) chronic (up to 3-year duration), slowly progressive [8,56,60] or relapsing-remitting [54] neuropathies preceded diagnoses of either indolent/low grade or diffuse large cell lymphoma, respectively; (d) a patient with a 2-year slowly progressive sensorimotor neuropathy developed B-cell CLL [49]; in this case, HTLV-1 co-infection could have triggered malignant transformation of an antigen-committed B-cell clone [61], or HTLV-1-infected T-cells activated autologous B-cells in a contact-dependent manner [62]. (2) In some patients lymphoma diagnosis preceded onset of neuropathy: (a) in 1 report, relapsing-remitting cranial polyneuropathy occurred in a patient with established cutaneous lymphoma in remission and subsequent recurrence [45]; (b) recurrent, treated [58,59] or indolent, untreated [60] lymphoma preceded the onset of neuropathy symptoms at intervals of 2 years, 10 and 6 months in 3 patients, respectively.…”
Section: Autoantibody-mediated Polyneuropathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…undetected lymphoma) developed fatal EBV+ intracerebral lymphoma after treatment with various courses of immunotherapy [46]; analyses of intrathecal and peripheral M-protein as well as brain immunocytochemical studies suggested a common clonal origin of both immunoblastic cerebral proliferation and the serum paraprotein-secreting cells. Presumably, immune deficiency due to monoclonal B-cell proliferation and/or immunosuppressive therapy resulted in EBV-reactivation and dysregulation of CNS-restricted T-cell control of B-cell proliferation; autopsy did not include search for systemic lymphoma; (c) chronic (up to 3-year duration), slowly progressive [8,56,60] or relapsing-remitting [54] neuropathies preceded diagnoses of either indolent/low grade or diffuse large cell lymphoma, respectively; (d) a patient with a 2-year slowly progressive sensorimotor neuropathy developed B-cell CLL [49]; in this case, HTLV-1 co-infection could have triggered malignant transformation of an antigen-committed B-cell clone [61], or HTLV-1-infected T-cells activated autologous B-cells in a contact-dependent manner [62]. (2) In some patients lymphoma diagnosis preceded onset of neuropathy: (a) in 1 report, relapsing-remitting cranial polyneuropathy occurred in a patient with established cutaneous lymphoma in remission and subsequent recurrence [45]; (b) recurrent, treated [58,59] or indolent, untreated [60] lymphoma preceded the onset of neuropathy symptoms at intervals of 2 years, 10 and 6 months in 3 patients, respectively.…”
Section: Autoantibody-mediated Polyneuropathiesmentioning
confidence: 99%
“…Serum paraprotein (IgMκ or λ) was detected in all but 4 patients [49,54,60]; however, 3 patients showed tri-clonal bands, specifically IgMκ/λ and IgGκ [47]; IgMκ and bi-IgGκ [50] or tri-IgMκ [58]. Serum mixed cryoglobulins were detected in 3 cases, and possibly played a pathogenic role in neuropathy in 2 patients [8], but were deemed causally unrelated to neuropathy in 1 patient [48].…”
Section: Autoantibody-mediated Polyneuropathiesmentioning
confidence: 99%
“…First, the onset of neurological symptoms differed among the patients. Neuropathy preceded the manifestations of malignant lymphoma in one case (6). In contrast, neuropathy occurred even after chemotherapy and at the time of recurrence of primary disease in another case (7).…”
Section: Discussionmentioning
confidence: 96%
“…Second, the classification of immune-mediated neuropathy as an acute pattern (GBS) or a chronic pattern (CIDP) also differed among the cases. Although one case had a CIDP-like course with repeated relapses and remissions over several years (6), the present case showed a GBS-like clinical course, which was a monophasic subacute illness with neurological deterioration and remission within 1 month. Third, the response to treatments and the prognosis also varied among the cases.…”
Section: Discussionmentioning
confidence: 98%
“…92 Patients with NHL and monoclonal gammopathy can develop typical CIDP or predominantly sensory neuropathies that are likely mediated by antibody activity of the monoclonal IgM against myelinassociated glycoprotein or gangliosides. 93,94 Conversely, neuropathies associated with large B-cell lymphomas may be caused by direct infiltration of the peripheral nerves (neurolymphomatosis). 95 In a recent study of 32 patients with neuropathy and NHL, 15 were considered to have neurolymphomatosis, whereas only 5 were paraneoplastic.…”
Section: Paraneoplastic Sensorimotor Neuropathiesmentioning
confidence: 99%